Pemanfaatan Batok Kelapa menjadi Cinderamata sebagai Alternatif Penanggulangan Kemiskinan - Rosramadhana Rosramadhana; Anisa Rodia Harahap (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2014)
Poverty can be  solved by various ways in which one of them conducted by using coconut shells  to be souvenirs that based on cultural values as an alternative method in decreasing poverty. Management of production does not spend more cost as the material used also could be found easily. Beside to help elevating economic of household producers, it also could be synergy with ‘go green’ program in recycling waste of coconut shells converting to high value objects. The souvenirs which have been produced, firstly would be sold to stakeholders such as wealther local communities, Non Governmental Organizations (NGOs), Regional-Owned Enterprise (ROEs), State-Owned Enterprises (SOEs), universities, and exported abroad.  Finally, using coconut shells to be cultural souvenirs, will have helped the Indonesia people as well as to know and to hold their culture